2000
DOI: 10.1001/archopht.118.8.1081
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Biomaterials for Glaucoma Drainage Devices<subtitle>Part 2</subtitle>

Abstract: Background: Inflammation associated with biomaterials may contribute to the failure of glaucoma drainage devices.Objective: To compare the inflammatory reaction associated with the insertion of Krupin silicone, Molteno polypropylene, and Acrosof end plates in the subconjunctival space of rabbits.Methods: Similar-sized glaucoma end plates made of 3 different biomaterials were sutured to the sclera in the superotemporal quadrant of the rabbit eye. Thirty eyes of 15 albino New Zealand rabbits were randomly assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(59 citation statements)
references
References 19 publications
2
54
0
2
Order By: Relevance
“…[10][11][12][13] This encapsulation reaction is similar to the tissue response observed around most polymer implants. 14,15 Fibrotic, minimally vascular capsule formation gradually increases outflow resistance from the drain and eventually results in increased intraocular pressure (IOP).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] This encapsulation reaction is similar to the tissue response observed around most polymer implants. 14,15 Fibrotic, minimally vascular capsule formation gradually increases outflow resistance from the drain and eventually results in increased intraocular pressure (IOP).…”
Section: Introductionmentioning
confidence: 99%
“…13 Ayyala et al in an animal experimental study showed that polypropylene is more inflammatory than silicone. 14 In addition to valve material, other factors may influence the success rate after implant glaucoma surgery. Greater surface of the end-plate of the valve may be associated with lower IOP, still with the upper limit of the surface area beyond which the valve implantation will stimulate a greater inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies in rabbits have shown that polypropylene and other rigid biomaterials were associated with significantly more inflammation than silicone. 6,8 Law et al 9 compared the results of 50 silicone and 49 polypropylene AGVs in refractory glaucoma over a period of 12 months and showed that silicone AGVs resulted in lower IOPs with the difference between both groups being statistically significant at 3 months. However, more non-tube-related complications were encountered in the silicone group.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models of glaucoma drainage devices, silicone was associated with less inflammation and fibrosis compared with polypropylene. 7,8 It is postulated that the less the encapsulation around the explant, the less the resistance will be to aqueous flow, thus yielding better intraocular pressure (IOP) control and a longer term success of the device. 6 Most clinical studies comparing silicone to polypropylene AGVs have been retrospective studies on adult eyes and showed better or similar results with the silicone AGV.…”
Section: Introductionmentioning
confidence: 99%